The Role of School Public Relations in Establishing Cooperation with DUDI to Increase the Absorption of Graduates of Muhammadiyah 1 Salam Vocational School - Hesti Risatina; Bambang Sudarsono; Enung Hasanah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The high unemployment rate among vocational school graduates indicates a gap between graduate competencies and the needs of the business and industrial world. This condition requires the strategic role of school public relations in establishing and managing sustainable cooperation with the business and industrial world in order to increase graduate employment. This study aims to analyze the role of school public relations in establishing cooperation with DUDI to improve graduate employment at SMK Muhammadiyah 1 Salam. This study uses a descriptive qualitative approach with a case study type. Data were collected through observation,in-depth interviews, and documentation with informants selected purposively, including the principal, vice principal for public relations and curriculum, Special Job Exchange (BKK) manager, department heads, and industry partners. Data analysis was conducted using Miles and Huberman’s interactive model, which included data reduction, data presentation, and conclusion drawing and was tested for validity through source and technique triangulation. The results showed that roleof public relations in increasing graduate employment was carried out through four main stages, namely planning, organizing, actuating and controlling. Public relations plays a mediating role in analyzing competency requirements, mapping DUDI partners, developing and implementing cooperation through MoU and conducting evaluations based on tracer studies. The cooperation established includes field work practices, industry classes, teaching factories, guestteachers, teache internships, and graduate recruitment. These findings indicate that the role of public relation, when managed systematically and collaboratively, contributes positively to increasing the absorption of vocational school graduates into the workforce.